2020
DOI: 10.30684/etj.v38i7a.653
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Fiber Ultrafiltration Membrane for Methyl Green Dye Removal

Abstract: In this study, the behavior of a Polyvinyl chloride (18 wt % PVC) hollowfiber ultrafiltration (UF) membrane for methyl green (MG) dye removalfrom aqueous solution was estimated by studying the influence of varyingthe operation conditions (the concentration of the dye and volumetric flowrate) to determine their impact on the separation processes (permeate fluxand rejection coefficient) at constant pressure and temperature. The PVCmembrane was characterized by scanning electron microscopy.Furthermore, tests of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The relatively low TOC removal efficiency indicates that textile wastewater contains low molecular weight organic matter [ 36 ]. Alardhi et al [ 37 ] confirmed the success of dye removal with UF hollow fiber membranes, and Sherhan et al [ 38 ] also indicate high removal of turbidity of 95% and TOC of 96%.…”
Section: Resultsmentioning
confidence: 97%
“…The relatively low TOC removal efficiency indicates that textile wastewater contains low molecular weight organic matter [ 36 ]. Alardhi et al [ 37 ] confirmed the success of dye removal with UF hollow fiber membranes, and Sherhan et al [ 38 ] also indicate high removal of turbidity of 95% and TOC of 96%.…”
Section: Resultsmentioning
confidence: 97%
“…SEM analyzes were performed to find the morphology of the support catalyst prepare (AMK) [19]. Figure 3 presents and indicates the superposition of alumina with meta-kaolin and the image shows that several objects of arrangement form the surface of the MK samples after cementation.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…It must therefore be effectively handled according to priority (Al-Tohamy et al 2022). To remove dyes, a number of separation methods, such as physical and chemical ones (membrane filtration, coagulation, flocculation, and adsorption) (Alardhi et al 2023) biological ones (anaerobic and aerobic treatment) (Vashisht et al 2022), and chemical ones (photo-Fenton reaction, ozonation) (Tanveer et al 2022). In order to completely mineralize hazardous and non-biodegradable molecules, heterogeneous photocatalysis is favored, circumventing the drawbacks of physical and biological approaches (Ashraf et al 2022).…”
Section: Introductionmentioning
confidence: 99%